Genetic diversity of Aedes aegypti from the Central and Cordillera departments of Paraguay, using ISSR-PCR markers - Brítez, Sady; Céspedes, Enmanuel; Ferreira, María; Vázquez, Fátima; Rodríguez, Cinthya; Herrera, Leidi; Gonzalez-Brítez, Nilsa (Medicina Clínica y Social, 2024)
Introduction: Aedes aegypti is an insect of the culicidae group, preferably anthropophilic, which acts as a vector of some arboviruses, such as dengue, Zika and chikungunya and yellow fever, with a wide distribution in the tropics and subtropics and responsible for major epidemic outbreaks in Paraguay. Urbanization, globalization and the lack of effective control favor their permanence. Studying the genetic diversity of this species will make it possible to evaluate the dynamics of its populations and its adaptation to environmental changes, to guide its control. Objective: To estimate the genetic diversity of Ae. aegypti populations in the Central and Cordillera departments of Paraguay using simple sequence inter-repeat markers (ISSR). Methodology: 40 female mosquitoes were selected. 20 from the Central department and 20 from the Cordillera department corresponding to the Humid Chaco region, Paraguay, were selected for amplification of ISSR genetic markers by PCR, using the primers Rhea-4, ISSR-7, ISSR1 and Ae-ISSR-6. The degree of segregation of the populations studied with an AMOVA and the differentiation between them with the FST fixation index were determined using the program Arlequin version 3.5.2.2. Results: Thirty-six loci were identified, 90.91% of them polymorphic. Most of the genetic differentiation was due to variations within populations and the fixation index between populations (FST = 0.0432). Discussion: It is possible that the diversity within the Central and Cordillera populations is due to the heterogeneous characteristics in terms of urbanism and semi-rurality and the existence of ecotones, where these populations circulate. The results revealed moderate interpopulation genetic differentiation, indicating that they are not completely genetically isolated.